Association between the presence of parental sleep disorder and sleep bruxism in children: a cross-sectional observational study (Research, Society and Development, 2022)
The present research aimed to evaluate the sleep quality of caregivers of child patients and the perception of sleep bruxism in children. After selection inclusion and exclusion criteria, children and their respective caregivers were evaluated, and children were investigated for the presence of bruxism and, in caregivers, the Pittsburgh questionnaire was applied to assess sleep patterns. To analyze the outcomes of the caregiver's sleep quality variables: good, bad and presence of sleep disorder, the Chi-Square test was used (* p < 0.05 - 95%). This study was registered according to the CEP protocol: 2,056,660. In total, 186 subjects were evaluated: 93 children aged between 4 and 10 years (mean 6.3 years), 48 of which were girls, and 93 adult caregivers, 82 of which were women. Of this total, most of them (46 individuals or 49.4%) had poor sleep quality, 27 caregivers (29.1%) had sleep disorders and a minority of them (20 caregivers or 21.5%) had a good sleep quality. When assessing sleep disorder in adults, a significant association was found between an increase in the frequency of reporting sleep bruxism and a poor caregiver's sleep quality (p=0.022*). It was concluded that caregivers with good sleep quality had a lower frequency of reports, while caregivers with poor sleep quality reported a higher frequency of SB in children.